Combination of peptide YY3-36 with GLP-1(7-36) amide causes an increase in first-phase insulin secretion after IV glucose - Tan,TM; Salem,V; Troke,RC; Alsafi,A; Field,BCT; De,Silva A; Misra,S; Baynes,KCR; Donaldson,M; Minnion,J; Ghatei,MA; Godsland,IF; et al. (Journal of Clinical Endocrinology and Metabolism, 2014)
Context: The combination of peptide YY (PYY) and glucagon-like peptide-1 (GLP-1) has been proposed as a potential treatment for diabetes and obesity. However, the combined effects of these hormones, PYY3–36 and GLP-17–36 amide, on glucose homeostasis are unknown.Objective: This study sought to investigate the acute effects of PYY3–36 and GLP-17–36 amide, individually and in combination, on insulin secretion and sensitivity.Setting and Design: Using a frequently sampled iv glucose tolerance test (FSIVGTT) and minimal modeling, this study measured the effects of PYY3–36 alone, GLP-17–36 amide alone, and a combination of PYY3–36 and GLP-17–36 amide on acute insulin response to glucose (AIRg) and insulin sensitivity index (SI) in 14 overweight human volunteers, studied in a clinical research facility.Results: PYY3–36 alone caused a small but nonsignificant increase in AIRg. GLP-17–36 amide alone and the combination of PYY3–36 and GLP-17–36 amide did increase AIRg significantly. No significant differences in SI were observed with any intervention.Conclusions: PYY3–36 lacks any significant acute effects on first-phase insulin secretion or SI when tested using an FSIVGTT. Both GLP-17–36 amide alone and the combination of PYY3–36 and GLP-17–36 amide increase first-phase insulin secretion. There does not seem to be any additive or synergistic effect between PYY3–36 and GLP-17–36 amide on first-phase insulin secretion. Neither hormone alone nor the combination had any significant effects on SI.